Metal halide perovskites-based white light-emitting diodes. (22nd September 2022) - Yao, Jisong; Xu, Leimeng; Wang, Shalong; Song, Jizhong
Abstract: White light-emitting diodes (WLEDs) serve as a replacement for traditional incandescent light due to their excellent characteristics, such as high brightness, efficiency in energy consumption, and long lifetime. The high-efficiency and low-cost white-emitting materials and light-emitting diode devices has always been the goal pursued in the field of lighting technology. Recently, metal halide perovskites are emerging as one of the most promising luminescent materials for next-generation WLEDs due to their facile synthesis and excellent optoelectronic properties, such as high photoluminescence quantum yields, widely tunable bandgap, and high charge-carrier mobility. Although the luminescence efficiency of perovskite emitters and WLED devices has increased rapidly over the past several years, achieving high-efficiency and stable WLEDs remains great challenges. In this review, we focus on the recent progresses of WLEDs based on metal halide perovskites including color-conversion WLEDs, tandem structure of WLEDs, double-emissive-layer of WLEDs, and single-emissive-layer of WLEDs. Importantly, we highlight the WLEDs based on a single emissive layer that show white electroluminescence directly from the perovskite emitters. Finally, we will give an outlook of future research avenues on how to reach the goal of efficient and stable perovskite-based WLEDs.